THE ROLE OF LEARNING STYLES IN STUDENTS’ ENGLISH ACADEMIC ACHIEVEMENT AT MTSN 2 TEMBILAHAN - Felci Tria Sauhana; Melda Yeni (JELLT (Journal of English Language and Language Teaching), 2021)
Abstract The goals of this research are to identify the role of learning styles in the MTsN 2 Tembilahan academic achievement of students in English and also to know whether or not they have some learning styles to absorb and understand lessons. The results of data analysis obtained that visual learning style has no significant effect on students achievement because t test = 1.700 < t table = 1.97519 with a significance level of 0.091. While Audio learning style has an effect on students’ achievement because t test = 6.195 > t table = 1.97519 with a significance level of 0.000. Then, kinesthetic learning style has an effect on student achievement because t count = 3.009 > t table = 1.97519 with a significance level of 0.003 the learning styles. Besides, simultaneously or simultaneously all independent variables affect the independent variables. This is because f table 25.260 is greater than f table = 2.66 with a significance level of 0.000 less than 0.05. It can also be said that the Visual, Audio and Kinesthetic variables have a simultaneous effect on the Students’ English Achievement variable. Keywords: Learning Style, Visual Learning Style, Auditory Learning Style, Kinesthetic Learning Style, Students Achievement